ANALISIS KEPUASAN MAHASISWA TERHADAP KUALITAS PEMBELAJARAN UNTUK MENINGKATKAN MUTU PENDIDIKAN TINGGI DI LLDIKTI WILAYAH IV - Maharani maharani; Fery Citra Febriyanto; Nisak Ruwah Ibnatur Husnul (Jurnal Administrasi Pendidikan, 2023)
This study aims to determine students' satisfaction toward the quality of learning as well as supporting and inhibiting factors in improving the quality of university in the LLDIKTI Wilayah IV area. The type of research used mix method approach, namely a qualitative quantitative approach. The research instrument is a questionnaire to obtain quantitative data, and interviews to obtain qualitative data. The population of this study were all collages students in the LLDIKTI Wilayah IV, for the sample used purposive sampling. The data analysis technique used correlation for quantitative and data triangulation for qualitative. The results of the study can be concluded that the distribution of questionnaires in LLDIKTI Wilayah IV area with 350 students randomly resulted in 1) The level of student satisfaction based on five dimensions, namely tangibles, responsiveness, reliability, empathy and assurance were categorized as satisfactory. 2) Supporting and inhibiting factors that affect student satisfaction with learning to improve the quality of education are from the SWOT analysis by looking at the strengths and opportunities that exist for supporting factors, and inhibiting factors from weaknesses and threats. 3) Strategies to improve the quality of education by creating a conducive academic atmosphere, increasing public confidence in the quality of education they have, improving the quality of lecturers and employees, compiling graduate output based on the concentration of each department, integrating the learning process well, improving service quality academics by maximizing information technology systems, improving the quality of learning infrastructure and increasing the quality of accreditation.